2016
DOI: 10.1002/bies.201600104
|View full text |Cite
|
Sign up to set email alerts
|

Peptide drugs accelerate BMP‐2‐induced calvarial bone regeneration and stimulate osteoblast differentiation through mTORC1 signaling

Abstract: Both W9 and OP3‐4 were known to bind the receptor activator of NF‐κB ligand (RANKL), inhibiting osteoclastogenesis. Recently, both peptides were shown to stimulate osteoblast differentiation; however, the mechanism underlying the activity of these peptides remains to be clarified. A primary osteoblast culture showed that rapamycin, an mTORC1 inhibitor, which was recently demonstrated to be an important serine/threonine kinase for bone formation, inhibited the peptide‐induced alkaline phosphatase activity. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…In the present study, we demonstrated that treatment of OPG –/– mice with W9 restored their alveolar bone loss through two independent mechanisms: One is suppression of osteoclastogenesis by inhibiting RANK signaling in osteoclast precursors, and the other is enhancement of osteoblastogenesis by suppressing sclerostin expression in osteocytes. In addition to W9, OP3-4, a cyclic peptide, to mimic OPG, was reported to bind to RANKL, thereby inhibiting osteoclastogenesis [ 33 ]. OP3-4 could accelerate bone formation by affecting RANKL signaling in osteoblasts in a similar manner to W9 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we demonstrated that treatment of OPG –/– mice with W9 restored their alveolar bone loss through two independent mechanisms: One is suppression of osteoclastogenesis by inhibiting RANK signaling in osteoclast precursors, and the other is enhancement of osteoblastogenesis by suppressing sclerostin expression in osteocytes. In addition to W9, OP3-4, a cyclic peptide, to mimic OPG, was reported to bind to RANKL, thereby inhibiting osteoclastogenesis [ 33 ]. OP3-4 could accelerate bone formation by affecting RANKL signaling in osteoblasts in a similar manner to W9 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to W9, OP3-4, a cyclic peptide, to mimic OPG, was reported to bind to RANKL, thereby inhibiting osteoclastogenesis [ 33 ]. OP3-4 could accelerate bone formation by affecting RANKL signaling in osteoblasts in a similar manner to W9 [ 33 ]. These results suggest that RANKL-binding peptides may have unique characteristics in the regulation of bone resorption and formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical application of recombinant human bone morphogenetic protein-2 (rhBMP-2), which is one of the most important bone inductive proteins, has been expected, and it has been approved for clinical use in extraction socket preservation and maxillary sinus floor augmentation 5) . rhBMP-2 shows superior bone regeneration, however, several adverse events have been reported such as local edema, seroma, and cancer induction at high-dose rhBMP-2 [6][7][8] . Atelocollagen sponge (ACS) is presently used as a carrier of rhBMP-2; however, it is reported to release rh-BMP-2 instantaneously 9) .…”
Section: Introductionmentioning
confidence: 99%